Sourdough bread innovation with green banana flour seen from its physical and sensory characteristics - Rahardjo, Monika; Sihombing, Monang; Carouline, Bintang; Budi, Regina Natasya; Asri, Elisabet Stefia (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: Green banana flour (GBF), rich in resistant starch and dietary fiber, has gained attention as a functional ingredient for improving gut health and metabolic regulation. While GBF has been applied in conventional bread, its effect on sourdough bread remains underexplored. This study aimed to evaluate the physical and sensory properties of sourdough bread incorporated with GBF. Methods: Sourdough bread was prepared using wheat flour (control, TC) and GBF substitution at 10% (TP1), 20% (TP2), and 30% (TP3), with identical hydration and processing conditions. Texture profile analysis was performed using a texture analyzer, while sensory evaluation was conducted with 50 untrained panellists using a 5-point hedonic scale. Data were analyzed by ANOVA followed by Duncan’s test (α = 5%). Results: Texture analysis revealed that increasing GBF substitution significantly elevated hardness, springiness, and stiffness, while reducing fracture force compared to TC. Sensory results indicated that TC scored the highest in all parameters, especially taste (4.20 ± 0.67) and overall acceptability (4.26 ± 0.76). TP1 remained acceptable, showing comparable scores to TC in aroma (3.68 ± 0.74) and texture (3.84 ± 0.57). However, TP2 and TP3 demonstrated lower consumer acceptance, with TP3 recording the lowest scores in taste (3.14 ± 0.78) and overall acceptability (3.36 ± 0.88). Conclusion: GBF incorporation modifies sourdough bread texture by increasing firmness and structural density, while sensory acceptance declines at higher substitution levels. Up to 10% GBF can be added without compromising consumer preference, offering potential for developing nutritionally enhanced sourdough bread.